Assessment of Water Quality Index for Agricultural (Irrigation and Livestock) Use in Jos Metropolis Plateau State, Nigeria (Journal of Pure and Applied Sciences (Science Forum), 2026)
The Jos Plateau is a major center of poultry production and greenhouse-based irrigation farming in Nigeria, where agricultural activities rely heavily on groundwater obtained from privately owned hand-dug wells and boreholes. This study evaluates the suitability of groundwater for irrigation and livestock uses in Jos-North Local Government Area using established agricultural water quality indices, including Sodium Adsorption Ratio (SAR), Kelly’s Ratio (KR), Residual Sodium Carbonate (RSC), Magnesium Adsorption Ratio (MAR), Permeability Index (PI), Potential Salinity (PS), Sodium Percentage (Na%), and Total Dissolved Solids (TDS). Thirty-three (33) groundwater samples were collected from handdug wells using sterilized 100 cl bottles. Field measurements of pH, temperature, electrical conductivity (EC), and TDS were conducted using calibrated handheld meters, while sampling coordinates were recorded with a Garmin 62 GPS. Laboratory analyses were performed using a BWB XP flame photometer for Ca²⁺, Na⁺, and K⁺, a HACH DR1900 portable spectrophotometer for Mg²⁺, SO₄²⁻, Cl⁻, and NO₃⁻, and titrimetric methods for HCO₃⁻. Results indicate that pH ranges from 6.45 to 9.78 (mean = 7.9), temperature from 22.5 to 35.1 °C (mean = 26.6 °C), EC from 60 to 3398 mS/m (mean = 901.1 mS/m), and TDS from 30 to 1699 mg/L (mean = 444.1 mg/L). The dominant ionic composition follows the order Na⁺ > Mg²⁺ > K⁺ > Ca²⁺ for cations and HCO₃⁻ > Cl⁻ > SO₄²⁻ > NO₃⁻ for anions. Pearson correlation analysis revealed notable nitrate associations, suggesting possible agricultural runoff influences. Irrigation water quality indices produced contrasting results. SAR classified 97% of samples as excellent, while RSC indicated 85% as safe, suggesting low sodium hazard. In contrast, MAR classified 88% of samples as harmful, with nearly half considered extremely harmful, indicating potential magnesium-induced soil permeability problems. This interpretation is supported by PI results, which classify over 63% of samples as moderate to poor, while Na% and KR categorize substantial proportions of samples as doubtful to unsuitable for irrigation. For livestock use, TDS-based assessment classified 87.1% of samples as excellent and 12.9% as very satisfactory. Overall, groundwater in the study area is suitable for livestock watering, but irrigation use may pose long-term soil management challenges, highlighting the need for integrated hydrochemical monitoring to support sustainable agricultural water management on the Jos Plateau.